5. KRISIS HARGA PANGAN GLOBAL DAN KEBIJAKAN BANTUAN PANGAN AMERIKA SERIKAT - Utomo, Tri Cahyo (Faculty of Social and Political Sciences Diponegoro University, 2009)
During the last two years, the price of food in global market increased significantly. Various factors, such as population growth, biofuels development, oil price rise, midlle class’ life style, urbanization, WTO’s stipulation, influenced the increase. Political protests, lauched by middle and lower classes, occured in many developing countries, especially in Africa and Asia. They demanded their governments decreasing the price soon. The US, as a rich country, introduces food and program for other countries under the PL 480. Yet, the program was criticized. In reality, it brought benefits for Americans mostly and did not contribute meaningfully decreasing the suffering of the poor in developing countries.